INCREASED REVENUE MOBILIZATION IN THE DEMOCRATIC REPUBLIC OF CONGO: ANALYSIS OF MEASURES TAKEN BY THE MINISTRY OF FINANCE AND PERSPECTIVES - MUKENGE KATUMBA , Guy-Sylvain; MAKUMBIZA USENI , Rodrigue (Revue du contrôle, de la comptabilité et de l’audit, 2022)
In the Democratic Republic of Congo, revenue mobilization is ensured under the responsibility of the Minister in charge of Finance; revenue mobilization actions are carried out by the Heads of the Financial Authorities, namely, the General Directorate of Taxes (DGI), the General Directorate of Customs and Excise (DGDA) and the General Directorate of Administrative, Judicial, State and Participation (DGRAD), in collaboration with Base Services. The objective of this article is to present the partial results of the actions taken by the Ministry of Finance for revenue mobilization for 2022 in the Democratic Republic of Congo and the outlook for 2023. To carry out this study, we used the comparative method which allowed us to take a comparative look at the assignments and achievements in the past and those of the first half of 2022.